Entrepreneurship Orientation for Building Business Performance: An Empirical Study Distro SME’s Bandung City - Limakrisna, Nandan; Sudarso, Andriasan; Daryus, Cecep (International Journal of Economics and Financial Issues, 2015)
he article aims to examine the influence of entrepreneurial orientation on buyers’ relationship, suppliers’ relationship, and complementary products relationship and the implications on business performance. The research method used was descriptive survey method and explanatory survey with a sample size of 200 respondents, namely entrepreneurs of Bandung City Distro. The results (findings) in this research were entrepreneurial orientation, buyers’ relationship, suppliers relationship, and complementary products relationship carried out by the entrepreneurs were quite good and can lead the high business performance of Distro entrepreneurs. The entrepreneurial orientation has effect on buyers’ relationship, suppliers’ relationship, and complementary products relationship. Likewise, buyer’s relationship, suppliers’ relationship, and complementary products relationship simultaneously affect on business performance. Complementary products relationship partially more dominant in influencing business performance. Keywords: Entrepreneurial Orientation; Relationship; Business Performance JEL Classifications: M21